Determinant of customers' switching behavior toward Bank Rakyat Ayer Keroh / Nurdiana Mohamad - Mohamad, Nurdiana Mohamad (2015)
This study is aimed to investigate the relationship and factors that influence customer switching behavior towards customer at Bank Rakyat Ayer Keroh, Melaka. Data collection is done by using questionnaire and involves 180 selected respondents for this study. The methods used in this study are reliability test, correlation coefficient, descriptive, multiple linear regressions to find the relationship between independent variable and dependent variable the factor that influence customer switching behavior. The findings show that there are some factors has relationship with customer switching behavior which is accessibility, strategic location, and cost and charge and only one factor that most influence customer switching behavior which is cost and charge.